The Effect of Al₂O₃ Nanoparticle Addition and Ultrasonic Vibration on Vehicle Radiator Heat Transfer Performance - SUGENG SUSILO; Diama Rizky Septiawan; Faradilla Fauziyah Risnawati; Agus Dwi Putra (Evrimata: Journal of Mechanical Engineering, 2026)
This study addresses the need for enhanced vehicle cooling systems as modern engines operate under increasingly harsh conditions, necessitating efficient heat dissipation to prevent overheating and optimize fuel efficiency. The aim of this research is to investigate the combined effect of adding Al₂O₃ nanoparticles and applying ultrasonic vibration on the heat transfer performance of automotive radiators. Experimental tests were conducted with various concentrations of Al₂O₃ nanoparticles, and ultrasonic vibrations were applied to assess their impact on fluid temperature, temperature differences across the radiator, and overall heat transfer rate. The results demonstrate that the addition of Al₂O₃ nanoparticles significantly improved the thermal conductivity and temperature differential (ΔT) between the inlet and outlet of the radiator. Furthermore, ultrasonic vibration enhanced heat transfer by disrupting the thermal boundary layer and increasing fluid turbulence. Notably, the combined use of both techniques resulted in a significant increase in the heat transfer coefficient (U) and the heat transfer rate (Q). These findings contribute to the existing body of knowledge by showing that the synergistic application of nanoparticles and ultrasonic vibrations offers an efficient solution for improving vehicle cooling systems without requiring substantial design changes.